The design of the internet of things for the application of making automatic fish feeders - Muhammad Irfan Sarif (INFOKUM, 2022)
Rapid technological advances must be utilized, studied and applied in everyday life. One of the technological advances that have been applied is in the field of control, currently with wireless network technology which has grown rapidly the problem of distance and time can be solved with wireless network technology. For example, the use of computer systems in everyday life. The use of a computer system will make performance in terms of distance and time more effective. Seeing the progress of wireless technology is not impossible in the future various kinds of electronic devices can be controlled via wireless technology. The research objective in this final project is to develop and create a control system with a wireless network using Bluetooth which can control fish feeding easily and quickly in feeding fish. The creation of an IOT (Internet Of Things) Based Fish Feeder robot using Bluetooth as a control actuator or servo motor signal delivery system. The servo motor will work if it receives input from the smartphone button as a medium to control the valve for the fish feed container which will be poured into the fish holding pond. The fish feeding system that the author has developed uses only two buttons to control the many servo motor movements to spill fish feed into the pond. The tools developed by the researchers have met the expectations of researchers and catfish breeders, because they are very beneficial for the effectiveness of catfish feeding activities.